Single institution, randomized study to compare the efficacy and safety between laparoendoscopic single-site (LESS) surgery and conventional laparoscopic surgery for uretero-pelvic junction (UPJ) stone - Ab. Rashid, Islah Munjih; Kwon, Ohseong; Cho, Sung Yong; Park, Yong Hyun; Son, Hwancheol; Kim, Hyeon Hoe (Elsevier, 2013)
LESS has slowly adopted its role in current urological practice. The objective of our study is to confirm the efficacy and safety of laparoendoscopic single-site surgery (LESS) compared to conventional laparoscopic surgery for upper urinary tract stones